Cholelithiasis and laparoscopic cholecystectomy: identifying the appropriate time for operative intervention - Kotecha, Ravi; Kotecha, Vishwa (International Surgery Journal, 2021)
Background: Cholelithiasis is the most common among hepatobiliary disease and often requires surgical intervention. Laparoscopic cholecystectomy is the gold standard nowadays. This research paper was done to know appropriate time for laparoscopic cholecystectomy and how much improvement will we get after laparoscopic cholecystectomy. Methods: In our prospective observational study, 118 patients of cholelithiasis, 59 with dyspepsia in one group and 59 without dyspepsia in another group were taken. Both groups patients were analysed with Bucklay validated dyspeptic score before and after laparoscopic cholecystectomy till 6 months postoperatively for score improvement. Results: In our study, we confirmed that there was improvement in Buckley validated dyspeptic score in both group of patients with dyspepsia and without dyspepsia 6 month after laparoscopic cholecystectomy but not complete improvement. Improvement in Buckley validated dyspeptic score 6 months after laparoscopic cholecystectomy was more in patients with less duration of symptoms and less frequency of episode preoperatively and in non-dyspeptic patients. Conclusions: We could conclude that even earlier surgery after onset of symptoms didn’t result in complete resolution of symptoms in both groups particularly in group B (patients with dyspepsia). We can say that weather it is dyspeptic or non-dyspeptic gallstone disease, it has benefit from laparoscopic cholecystectomy but we can also say that improvement achieved is not complete as after laparoscopic cholecystectomy there were still number of patients who had Buckley validated score more than 6 in both groups after 6 months of surgery.